PENGAPLIKASIAN GAYA PEMBELAJARAN VAK BAGI PEMBELAJARAN BUDAYA MELAYU DALAM KALANGAN PELAJAR DI TUFS, JEPUN - Muhd Zulkipli, Noor Zuhidayah; Wan Mohamad, Wan Muna Ruzanna; Surat, Shahlan (JURNAL MELAYU SEDUNIA, 2019)
Language teaching and learning need to include cultural aspects to help students not only master the linguistic aspects but also the cultural aspects. Therefore, in order to promote cultural integration in language education, teachers need to be aware of students' learning styles toward cultural aspects. This is to ensure that the cultural teaching approach used by the teacher matches the student's learning style towards cultural aspects. One of the most popular learning styles is the Visual-Auditory-Kinesthetic learning styles that engage students’ senses in learning. In this regard, this study was conducted to investigate the learning styles towards Malay culture in the teaching and learning Malay as a foreign language. This study was conducted at the Tokyo University of Foreign Studies (TUFS), Japan. Data was collected using a questionnaire. A total of 30 students involved in this study. The result of this study showed that students in TUFS, Japan preferred audio learning style (mean=3.35), followed by visual learning style (mean=2.70) and kinesthetic learning style (mean=2.40). The study also revealed that the students always speak with the native speakers of Malay language (mean = 4.13, SD = 1.01) to learn Malay culture. The implications of this study can help teachers and students be aware of and understand the students’ learning styles towards Malay culture, thus helping the process of Malay language teaching and learning become more meaningful and effective.